2022
DOI: 10.1101/2022.12.23.521843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymmetric HIV-1 envelope trimers bound to one and two CD4 molecules are intermediates during membrane binding

Abstract: Human immunodeficiency virus 1 (HIV-1) infection is initiated by binding of the viral envelope glycoprotein (Env) to the cell-surface receptor CD4. Although high resolution structures of Env complexed with soluble domains of CD4 have been determined, the binding process is less understood on native membranes. Here, we apply cryo-electron tomography (cryo-ET) to monitor Env-CD4 interactions at membrane-membrane interfaces formed between HIV-1 and CD4-presenting virus-like particles. Env-CD4 complexes organized … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…These results provide further evidence of native-like soluble SOSIP Env trimers resembling their virion-bound counterparts 4,5 , both in the closed, prefusion conformation and in various CD4-bound conformations that adopt different conformations compared with unliganded Env trimers. Thus, this and the accompanying cryo-ET study 41 , together with previous Env structures, complete a description of the conformations of HIV-1 Env trimers at each stage of engaging CD4, starting with no bound receptors to the final conformation with three bound receptors (Fig, 5; Supplementary Movie 1).…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…These results provide further evidence of native-like soluble SOSIP Env trimers resembling their virion-bound counterparts 4,5 , both in the closed, prefusion conformation and in various CD4-bound conformations that adopt different conformations compared with unliganded Env trimers. Thus, this and the accompanying cryo-ET study 41 , together with previous Env structures, complete a description of the conformations of HIV-1 Env trimers at each stage of engaging CD4, starting with no bound receptors to the final conformation with three bound receptors (Fig, 5; Supplementary Movie 1).…”
Section: Discussionmentioning
confidence: 75%
“…We found that binding of one CD4 resulted in minor structural changes to a native-like soluble Env trimer in the closed, prefusion state; for example, we did not observe opening of any of the gp120 subunits of the trimer or the accompanying changes in the CD4-bound gp120 that result from CD4 associating with gp120 in CD4-bound open trimers [6][7][8][9][10] (in particular, changes resulting from insertion of Phe43CD4 into a gp120 hydrophobic cavity, which facilitates induced changes such as V1V2 displacement in CD4-bound gp120 subunits of fully-saturated open Env trimers [6][7][8]23,24 , were minor). By contrast, the one CD4-bound conformation of membrane-bound Env trimer revealed by cryo-ET/sub-tomogram averaging showed a partially open conformation in which the CD4-bound protomer appeared to undergo CD4-induced conformational changes 41 .…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations